Індивідуалізація антибактеріальної терапії тяжкої негоспітальної пневмонії з урахуванням системного запалення та імунного статусу - Т. О. Pertseva; K. O. Bielosludtseva (Medičnì Perspektivi, 2013)
Individualization of antibiotic therapy (ABT) of patients with severe community-acquired pneumonia (CAP) is a key issue in the world. Today the role of various biomarkers in ABT individualization in patients with CAP, including markers of systemic inflammation and cellular immunity is vividly discussed. But their variability at different etiological factors of CAP according to the immunological reactivity of patients was not studied at all. That’s why the aim of our study was to evaluate the diagnostic value of marker of systemic inflammation procalcitonin (PCT) and marker of cellular immunity CD4+ in patients with severe CAP, considering etiological factor and their role in individualization of antibiotic preparation (ABP) choice in these patients. A study group consisted of patients with severe CAP without HIV and identified respiratory pathogen. Comparison group consisted of HIV-positive persons, who accounted nearly 17% of all the patients. According to the results of this work it was revealed that in all patients CAP was accompanied with marked inflammatory response (which is confirmed by 250 times higher than normal serum PCT (level) and severe immunodeficiency state, even in HIV absence. The markers changed depending on CAP etiology. In CAP caused by Gr(-) pathogens PCT levels was 500 times higher than normal, and the number of CD4+ was less than normal in all patients. Conclusions: 1) reduced number of CD4, less than 200 ml-1 in patients with severe CAP, accompanied by a sharp increase in serum PCT level is a marker of Gr(-) respiratory pathogen; 2) the imbalance between clinical symptoms and normal serum PCT level against a sharp decline in CD4+number is an indication to search for HIV and administration of the antipneumocystic therapy.